Lithium iron phosphate positive electrode material, preparation method thereof and lithium battery
By using lithium iron phosphate seeds and carbon sources with different compaction densities, combined with sand grinding and sintering processes, the problem of taking into account the high compaction density and rate performance of lithium iron phosphate materials is solved, and the high compaction of the material is achieved Synergistic improvement of density and better rate performance.
Patent Information
- Application Number
- CN202411722360.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-27
- Publication Date
- 2025-01-10
AI Technical Summary
The existing lithium iron phosphate positive electrode materials are difficult to take into account both high compaction density and rate performance, and cannot improve their rate performance while ensuring high compaction density.
Two lithium iron phosphate of different compaction densities are used as seeds, and lithium iron phosphate of locally different compaction densities are formed through sand grinding and sintering processes. Lithium iron phosphate of low compaction densities is filled in the gap of high compaction density. Combine carbon sources and surfactants to improve the overall performance of the material.
It has achieved good rate performance on the basis of ensuring high compaction density, and the process is simple and convenient for mass production.
Smart Images

Figure BDA0005159394280000091
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of lithium batteries, and in particular to a lithium iron phosphate positive electrode material and a preparation method thereof, and a lithium battery. Background Art
[0002] Lithium-ion batteries have been widely used in power tools, electric vehicles and energy storage due to their advantages such as high voltage platform, high energy density, no memory effect and long cycle life. As the positive electrode material of lithium-ion batteries, lithium iron phosphate material has excellent safety performance and cycle performance, is environmentally friendly, and is considered to be a highly potential power lithium-ion battery material. It has been a hot spot for development and research in recent years. In order to further improve the energy density of lithium-ion batteries, it is necessary to increase the specific capacity and compaction density of lithium iron phosphate. The existing improvement methods mainly include reducing carbon content, increasing roasting temperature, and particle grading. Although high-density lithium iron phosphate can be obtained, the current high-density lithium iron phosphate positive electrode materials generally have the problem of poor rate performance.
[0003] In recent years, with the vigorous development of the electric vehicle industry, the demand for fast charging and discharging capabilities of batteries has become increasingly urgent. It is of great significance to improve the rate performance of lithium iron phosphate positive electrode materials while ensuring the high compaction density of lithium iron phosphate materials, so that they have both high compaction density and good rate performance.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The first purpose of the present invention is to provide a method for preparing a lithium iron phosphate positive electrode material to solve the technical problem in the prior art that it is difficult for lithium iron phosphate positive electrode materials to have both high compaction density and good rate performance. The method of the present invention adopts two lithium iron phosphates with different compaction densities as seeds to prepare a lithium iron phosphate positive electrode material with both high compaction density and good rate performance.
[0006] The second object of the present invention is to provide a lithium iron phosphate positive electrode material, which is prepared by the preparation method of the lithium iron phosphate positive electrode material as described above.
[0007] A third object of the present invention is to provide a lithium battery comprising the lithium iron phosphate positive electrode material as described above.
[0008] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:
[0009] A method for preparing a lithium iron phosphate positive electrode material comprises the following steps:
[0010] The ferric phosphate, lithium source, carbon source, lithium iron phosphate seed crystals, additives and surfactants are mixed with a solvent to obtain a slurry, and the slurry is sand-milled, dried and sintered to obtain the lithium iron phosphate positive electrode material;
[0011] The lithium iron phosphate seed crystals include a first seed crystal and a second seed crystal, and the compaction density of the first seed crystal is greater than the compaction density of the second seed crystal.
[0012] Preferably, the mass ratio of the first seed crystal to the second seed crystal is 3:1-1:3.
[0013] Preferably, the compacted density of the first seed crystal is 2.45-2.55 cm 3 / g;
[0014] And / or, the compaction density of the second seed crystal is 1.95-2.15cm 3 / g.
[0015] Preferably, the amount of the lithium iron phosphate seed crystals added is 1%-20% of the mass of the iron phosphate.
[0016] Preferably, the iron phosphate and the lithium source are measured at a molar ratio of Li element to P element of 1.0-1.03.
[0017] Preferably, the added amount of the carbon source is 10%-20% of the mass of the ferric phosphate.
[0018] Preferably, the lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium acetate, lithium dihydrogen phosphate or lithium citrate.
[0019] Preferably, the carbon source comprises at least one of glucose, sucrose, citric acid, ascorbic acid, starch, polyethylene glycol, polyvinyl alcohol, sodium dodecyl sulfate, polyvinyl pyrrolidone phenolic resin and hexamethylenetetramine.
[0020] Preferably, the additive includes at least one of aluminum hydroxide, zirconium oxide, titanium dioxide, magnesium hydroxide, and niobium pentoxide.
[0021] Preferably, the surfactant includes at least one of polyethylene glycol, polyvinyl alcohol, sodium dodecyl sulfate, polyvinyl pyrrolidone phenolic resin and hexamethylenetetramine.
[0022] Preferably, the solid content of the slurry is 35%-45%.
[0023] Preferably, the particle size after sand grinding is 400-600 nm.
[0024] Preferably, the sintering temperature is 720-850° C., the heating rate is 1-5° C. / min, and the holding time is 6-12 h.
[0025] A lithium iron phosphate positive electrode material is prepared by the method for preparing a lithium iron phosphate positive electrode material described in any one of the aforementioned embodiments.
[0026] A lithium battery comprises the lithium iron phosphate positive electrode material described in the foregoing embodiment.
[0027] Compared with the prior art, the present invention has the following beneficial effects:
[0028] The present invention uses lithium iron phosphate with different compaction densities as seed crystals. At the same sintering temperature, the precursor is affected by the addition of seed crystals, thereby forming lithium iron phosphate with different local compaction densities. After crushing, the lithium iron phosphate with low compaction density in the lithium iron phosphate material is filled in the gap of the lithium iron phosphate with high compaction density, thereby ensuring the overall compaction density of the lithium iron phosphate material. Among them, the lithium iron phosphate seed crystal with high compaction density helps to improve the compaction density of the lithium iron phosphate material, and the lithium iron phosphate seed crystal with low compaction density helps to improve the rate performance of the lithium iron phosphate material. The two work synergistically, so that the prepared lithium iron phosphate material has good rate performance while ensuring high compaction density. DETAILED DESCRIPTION
[0029] The technical scheme of the present invention will be clearly and completely described below in conjunction with specific embodiments, but it will be appreciated by those skilled in the art that the following described embodiments are part of embodiments of the present invention, rather than all embodiments, and are only used to illustrate the present invention, and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work, all belong to the scope of protection of the present invention. If specific conditions are not indicated in the embodiments, they are carried out according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0030] A first aspect of the present invention provides a method for preparing a lithium iron phosphate positive electrode material, comprising the following steps:
[0031] The ferric phosphate, lithium source, carbon source, lithium iron phosphate seed crystal, additive and surfactant are mixed with a solvent to obtain a slurry, and the slurry is sand-milled, dried and sintered to obtain a lithium iron phosphate positive electrode material;
[0032] The lithium iron phosphate seed crystals include a first seed crystal and a second seed crystal, and the compaction density of the first seed crystal is greater than the compaction density of the second seed crystal.
[0033] The present invention uses lithium iron phosphate with different compaction densities as seeds. At the same sintering temperature, the precursor is affected by the addition of seeds, thereby forming lithium iron phosphate with different local compaction densities. After crushing, the lithium iron phosphate with low compaction density in the lithium iron phosphate material is filled in the gap of the lithium iron phosphate with high compaction density, thereby ensuring the overall compaction density of the lithium iron phosphate material. The performance of the material is consistent with the seeds added thereto. Affected by the high compaction lithium iron phosphate seeds (first seeds), the prepared lithium iron phosphate has a higher compaction density; affected by the lower compaction lithium iron phosphate seeds (second seeds), the prepared lithium iron phosphate has better rate performance. The method of the present invention uses the synergistic induction effect of the first seeds and the second seeds, so that the prepared lithium iron phosphate material has both a high compaction density and good rate performance; and the preparation process of the method of the present invention is simple and convenient for mass production.
[0034] In some specific embodiments of the present invention, the mass ratio of the first seed crystal to the second seed crystal is 3:1-1:3, for example, it can be any point value among 3:1, 2:1, 1:1, 1:2, 1:3 or a range value consisting of any two point values. The ratio of the first seed crystal to the second seed crystal will affect the overall compaction density and electrochemical performance of the induced lithium iron phosphate. If the first seed crystal accounts for too much, the electrochemical performance of the lithium iron phosphate material will decrease. If the second seed crystal accounts for too much, the compaction density of the lithium iron phosphate material will decrease. Only when the ratio of the first seed crystal to the second seed crystal is controlled within a suitable range, can the prepared lithium iron phosphate material have both high compaction density and good rate performance.
[0035] In some specific embodiments of the present invention, the compaction density of the first seed crystal is 2.45-2.55 cm 3 / g, for example, can be 2.45cm 3 / g, 2.46cm 3 / g, 2.48cm 3 / g, 2.5cm 3 / g, 2.52cm 3 / g, 2.54cm 3 / g, 2.55cm 3 / Any point value or a range of values consisting of any two point values in g;
[0036] and / or, the compacted density of the second seed crystal is 1.95-2.15 cm 3 / g, for example, can be 1.95cm 3 / g, 2.0cm 3 / g, 2.05cm 3 / g, 2.1cm 3 / g, 2.15cm 3 Any point value or a range of values consisting of any two point values in / g.
[0037] The compaction density of the first seed crystal and the second seed crystal will affect the overall compaction density and rate performance of the induced lithium iron phosphate material. Controlling the compaction density of the first seed crystal and the second seed crystal within the above range will help to obtain better overall performance.
[0038] In some specific embodiments of the present invention, the amount of lithium iron phosphate seed crystals added is 1%-20% of the mass of iron phosphate, for example, it can be any point value among 1%, 5%, 10%, 15%, 20% or a range value consisting of any two point values.
[0039] In some specific embodiments of the present invention, the iron phosphate and the lithium source are measured at a molar ratio of Li element to P element of 1.0-1.03.
[0040] In some specific embodiments of the present invention, the added amount of carbon source accounts for 10%-20% of the mass of ferric phosphate, for example, it can be any point value among 10%, 13%, 15%, 18%, 20% or a range value consisting of any two point values.
[0041] In some specific embodiments of the present invention, the lithium source used includes at least one of lithium hydroxide, lithium carbonate, lithium acetate, lithium dihydrogen phosphate or lithium citrate.
[0042] In some specific embodiments of the present invention, the carbon source used includes at least one of glucose, sucrose, citric acid, ascorbic acid, starch, polyethylene glycol, polyvinyl alcohol, sodium dodecyl sulfate, polyvinyl pyrrolidone phenolic resin and hexamethylenetetramine.
[0043] The carbon source can act as a reducing agent, reducing trivalent iron to divalent ferrous iron during the reaction; the residual carbon can also be coated on the surface of lithium iron phosphate particles, thereby improving the electrical conductivity of the material.
[0044] In some specific embodiments of the present invention, the additive includes at least one of aluminum hydroxide, zirconium oxide, titanium dioxide, magnesium hydroxide, and niobium pentoxide.
[0045] In some specific embodiments of the present invention, the surfactant used includes at least one of polyethylene glycol, polyvinyl alcohol, sodium dodecyl sulfate, polyvinyl pyrrolidone phenolic resin and hexamethylenetetramine.
[0046] In some specific embodiments of the present invention, the solvent used includes at least one of water, ethanol, methanol and acetone.
[0047] In some specific embodiments of the present invention, the solid content of the slurry is 35%-45%, for example, it can be any point value among 35%, 37%, 39%, 41%, 43%, 45% or a range value consisting of any two point values.
[0048] In some specific embodiments of the present invention, the particle size after sand grinding is 400-600 nm, for example, it can be any point value among 400 nm, 450 nm, 500 nm, 550 nm, 600 nm or a range value consisting of any two point values.
[0049] In some specific embodiments of the present invention, the drying method is spray drying.
[0050] In some specific embodiments of the present invention, the sintering temperature is 720-850°C, for example, it can be any point value among 720°C, 740°C, 760°C, 780°C, 800°C, 820°C, and 850°C, or a range value consisting of any two point values; the heating rate is 1-5°C / min, for example, it can be any point value among 1°C / min, 2°C / min, 3°C / min, 4°C / min, and 5°C / min, or a range value consisting of any two point values; the holding time is 6-12h, for example, it can be any point value among 6h, 7h, 8h, 9h, 10h, 11h, and 12h, or a range value consisting of any two point values.
[0051] The second aspect of the present invention provides a lithium iron phosphate positive electrode material, which is prepared by the preparation method of the lithium iron phosphate positive electrode material described in any one of the above embodiments. The lithium iron phosphate positive electrode material provided by the present invention has both high compaction density and good rate performance.
[0052] A third aspect of the present invention provides a lithium battery, comprising the lithium iron phosphate positive electrode material described in the foregoing embodiment.
[0053] The following is a detailed description of some embodiments of the present invention in conjunction with specific examples. The raw materials used in the examples can be purchased from the market unless otherwise specified.
[0054] Example 1
[0055] (1) According to the mass percentage, 100 parts of iron phosphate, 25 parts of lithium carbonate, 4 parts of sucrose, 0.4 parts of titanium dioxide, 9 parts of polyethylene glycol (PEG6000), and a compacted density of 2.50 cm 3 5 parts of the first seed crystal with a compacted density of 2.10 cm 3 / g of the second seed crystal 5 parts and 200 parts of water, and fully mixed to obtain slurry A;
[0056] (2) Grinding slurry A in a coarse grinding tank to obtain slurry B, transferring slurry B to a nano sand mill and grinding to obtain slurry C, the particle size after sand grinding is 420 nm;
[0057] (3) The slurry C was then spray dried and sintered, wherein the air inlet temperature of the spray drying was 240°C, the air outlet temperature was 90°C, and the sintering conditions were a heating rate of 3°C / min, the temperature was raised to 760°C, and the temperature was kept for 9 hours to obtain a lithium iron phosphate positive electrode material.
[0058] Example 2
[0059] Embodiment 2 is basically the same as Embodiment 1, except that:
[0060] In step (1), the amount of the first seed crystal used is 15 parts by mass, and the amount of the second seed crystal used is 5 parts by mass, and the other conditions are the same as those in Example 1.
[0061] Example 3
[0062] Embodiment 3 is basically the same as Embodiment 1, except that:
[0063] In step (1), the amount of the first seed crystal used is 5 parts by mass, and the amount of the second seed crystal used is 15 parts by mass, and the other conditions are the same as those in Example 1.
[0064] Example 4
[0065] Embodiment 4 is substantially the same as Embodiment 1, except that:
[0066] In step (1), the amount of the first seed crystal used is 10 parts by mass, and the amount of the second seed crystal used is 10 parts by mass, and the other conditions are the same as those in Example 1.
[0067] Example 5
[0068] Embodiment 5 is basically the same as Embodiment 1, except that:
[0069] In step (1), the amount of the first seed crystal used is 2.5 parts by mass, and the amount of the second seed crystal used is 2.5 parts by mass, and the other conditions are the same as those in Example 1.
[0070] Example 6
[0071] Embodiment 6 is basically the same as Embodiment 1, except that:
[0072] In step (1), the compacted density of the first seed crystal is 2.65 cm 3 / g, and the other conditions are the same as those in Example 1.
[0073] Example 7
[0074] Embodiment 7 is substantially the same as Embodiment 1, except that:
[0075] In step (1), the compacted density of the second seed crystal is 1.85 cm 3 / g, and the other conditions are the same as those in Example 1.
[0076] Comparative Example 1
[0077] Comparative Example 1 is substantially the same as Example 1, except that:
[0078] In step (1), no lithium iron phosphate seed crystals were added, and the other conditions were the same as those in Example 1.
[0079] Comparative Example 2
[0080] Comparative Example 2 is substantially the same as Example 1, except that:
[0081] In step (1), the amount of the first seed crystal added was 10 parts, and the second seed crystal was not added. The other conditions were the same as those in Example 1.
[0082] Comparative Example 3
[0083] Comparative Example 3 is substantially the same as Example 1, except that:
[0084] In step (1), the first seed crystal was not added, the amount of the second seed crystal added was 10 parts, and the other conditions were the same as in Example 1.
[0085] Test example
[0086] The compaction density of the lithium iron phosphate positive electrode material prepared in each embodiment and each comparative example was tested; and the lithium iron phosphate positive electrode material prepared in each embodiment and each comparative example was used to prepare a positive electrode sheet, assemble a battery, and perform an electrochemical performance test. The battery assembly process and test conditions are as follows:
[0087] Battery assembly: Using NMP as solvent, adjust the mass ratio of lithium iron phosphate, binder (PVDF-hsv-900) and conductive agent (SP) to 92:3:5 respectively, and then slurry it. Then use aluminum foil as current collector to coat it on an infrared flat plate coater. After the sample is vacuum dried, roll, die-cut, select and weigh it to obtain the positive electrode. The weighed electrode is transferred to the glove box for button battery assembly. The button battery shell uses CR2032 model, the negative electrode uses lithium sheet, and the electrolyte is Cyber electrolyte.
[0088] Electrochemical performance test: The assembled button cell was tested for electrochemical performance using the Blue Electric test system, and the test constant temperature cabinet was set to 25°C. The voltage range was set to 2.0-3.75V, and the cut-off current was calculated based on the mass of active material in each electrode and the measured rate.
[0089] Compacted density test: Use a powder automatic compaction density meter and refer to the national standard GB / T 24533-2009 to perform compacted density test. After the instrument is reset, weigh 1g±0.0050g of sample, test at a pressure of 3000kg, constant pressure time of 30s, and record the results.
[0090] The test results are shown in Table 1.
[0091] Table 1
[0092]
[0093] From the data in Table 1, we can see that compared with lithium iron phosphate prepared without adding seed crystals, adding lithium iron phosphate with high compaction density can indeed significantly improve the compaction density of the material, but the electrochemical performance of the material is poor. Adding lithium iron phosphate with low compaction density can also significantly improve the rate performance of the material, but the compaction density of the material is difficult to guarantee. Combining the two can optimize the rate performance of the material on the basis of ensuring the compaction density of the material, and successfully prepare a lithium iron phosphate cathode material that takes into account both compaction density and rate performance.
[0094] Although the present invention has been illustrated and described with specific embodiments, it should be appreciated that the above embodiments are only used to illustrate the technical solutions of the present invention rather than to limit it. Those skilled in the art should understand that the technical solutions described in the above embodiments may be modified, or some or all of the technical features thereof may be replaced by equivalents without departing from the spirit and scope of the present invention. However, these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present invention. Therefore, this means that all such replacements and modifications within the scope of the present invention are included in the appended claims.
Claims
1. A method for preparing a lithium iron phosphate positive electrode material, characterized in that: The following steps are involved: The ferric phosphate, lithium source, carbon source, lithium iron phosphate seed crystals, additives and surfactants are mixed with a solvent to obtain a slurry, and the slurry is sand-milled, dried and sintered to obtain the lithium iron phosphate positive electrode material; The lithium iron phosphate seed crystals include a first seed crystal and a second seed crystal, and the compaction density of the first seed crystal is greater than the compaction density of the second seed crystal.
2. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: The mass ratio of the first seed crystal to the second seed crystal is 3:1-1:
3.
3. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: The compacted density of the first seed crystal is 2.45-2.55 cm 3 / g; And / or, the compaction density of the second seed crystal is 1.95-2.15cm 3 / g.
4. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: The amount of the lithium iron phosphate seed crystal added is 1%-20% of the mass of the iron phosphate.
5. The method for preparing the lithium iron phosphate positive electrode material according to claim 1, characterized in that: The iron phosphate and the lithium source are measured at a molar ratio of Li element to P element of 1.0-1.
03.
6. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: The added amount of the carbon source is 10%-20% of the mass of the iron phosphate.
7. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: Contains at least one of the following characteristics: (1) The lithium source includes at least one of lithium hydroxide, lithium carbonate, lithium acetate, lithium dihydrogen phosphate or lithium citrate; (2) the carbon source comprises at least one of glucose, sucrose, citric acid, ascorbic acid, starch, polyethylene glycol, polyvinyl alcohol, sodium dodecyl sulfate, polyvinyl pyrrolidone phenolic resin and hexamethylenetetramine; (3) The additive includes at least one of aluminum hydroxide, zirconium oxide, titanium dioxide, magnesium hydroxide, and niobium pentoxide; (4) The surfactant includes at least one of polyethylene glycol, polyvinyl alcohol, sodium dodecyl sulfate, polyvinyl pyrrolidone phenolic resin and hexamethylenetetramine.
8. The method for preparing a lithium iron phosphate positive electrode material according to claim 1, characterized in that: Contains at least one of the following characteristics: (1) The solid content of the slurry is 35%-45%; (2) The particle size after sand grinding is 400-600 nm; (3) The sintering temperature is 720-850°C, the heating rate is 1-5°C / min, and the holding time is 6-12h.
9. A lithium iron phosphate positive electrode material, characterized in that: The lithium iron phosphate positive electrode material is prepared by the preparation method of any one of claims 1 to 8.
10. A lithium battery, characterized in that: Including the lithium iron phosphate positive electrode material as described in claim 9.